Methyl Violet Degradation Using Photocatalytic and Photoelectrocatalytic Processes Over Graphite/PbTiO3 Composite - Candra Purnawan; Sayekti Wahyuningsih; Vaishnavita Nawakusuma (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Photocatalytic and photoelectrocatalytic degradation of methyl violet dye using Graphite/PbTiO3 composites has been conducted. The purposes of this research were to examine photocatalytic and photoelectrocatalytic degradation of methyl violet using Graphite/PbTiO3 composite. Synthesis of         Graphite/PbTiO3 composite was successfully performed via sol-gel method by mixing graphite powder, titanium tetra isopropoxide precursor solution (TTIP) and Pb(NO3)2. The Graphite/PbTiO3 composites were characterized using X-Ray Diffraction (XRD), Fourier Transform-Infra Red (FT-IR), and Scanning Electron Microscopy (SEM). The XRD diffractogram and IR spectrum of Graphite/PbTiO3 composite revealed all characteristic peak of graphite and PbTiO3. Photocatalytic degradation process showed that Graphite/PbTiO3 composite with ratio 1/1 decreased concentrations of methyl violet up to 92.20 %. While photoelectrocatalytic degradation processed for 30 minutes at neutral pH and 10 V voltage degraded the methyl violet until 94 %. However, the photoelectrocatalysis is still not significance to improve methyl violet degradation compared with photocatalysis.